Patients' perspectives on three-monthly administration of antipsychotic treatment with paliperidone palmitate – a qualitative interview study. (4th May 2021) - Rise, Marit B.; Stølan, Liv Os; Erdner, Anette; Hedberg, Berith; Stahl, Katja; Riise, Jesper; Jedenius, Erik; Møllerhøj, Jette
Abstract: Introduction: Three-monthly dosage of paliperidone palmitate entails longer time to relapse after discontinuation, is similarly tolerable and safe compared to monthly injections of paliperidone palmitate and is beneficial for the caregivers. However, few studies have so far explored in depth the patients' experiences with paliperidone palmitate medication every three months, or with switching from monthly to three-monthly injections of paliperidone palmitate. Material and methods: A qualitative study based on individual interviews with persons with schizophrenia who receive three-monthly paliperidone palmitate in Norway, Sweden and Denmark. Data was analysed according to qualitative content analysis. Results: Twenty-four patients, 16 men and 8 women, took part in individual interviews. The patients' mental health care professionals mainly recommended the switch to three-monthly paliperidone palmitate, and few or no disadvantages were described. According to the patients, three-monthly paliperidone palmitate had several advantages, such as less frequent injections, less administration and planning and less focus on the illness. In addition, the participants described feeling more stability, being more physically and socially active, and that improvement processes were supported. For some, the use involved practical and economic challenges, and some worried whether the medicine 'wore off' before the next injection. According to the patients, switching to three-monthly paliperidone palmitate did not influence the frequency or content of patients' interaction with health care professionals. Conclusion: Switching from monthly to three-monthly injections with paliperidone palmitate seems to be experienced as advantageous for patients with schizophrenia.